Exploring a Simple Visualization Tool for Improving Conceptual Understanding of Classical Beam Theory. (2016) - Johnsen, Eivind; Nilsen, Magnus; Hjelseth, Eilif; Merschbrock, Christoph
Abstract: First year students struggle to understand the concepts in introductory engineering physics courses. Computer generated visualizations have proven their value for improving learning in tertiary education. However, it remains often unclear how visualization software can be effectively deployed in classrooms to best improve learning outcomes. In this paper we put a freshly developed educational software entitled "The virtual beam demonstrator" to a first test in a physics and mechanics lecture at Oslo University College. The intention of this work was to explore how to get the balance between technology, pedagogics, and content knowledge right to best support student learning. We evaluated student learning outcomes of our initial attempt to use the software in a classroom based on a student evaluation form. While initial results are promising, we cannot claim to have significantly improved student learning in our initial attempt at using the software. The evaluations showed only slight improvement in conceptual understanding by the students. This finding was not unexpected as we anticipated that finding the right approach for putting this softwareto usewould takeseveral attempts. To turn failure into success, we would need astrongeremphasison customized pedagogic methods. Relevant theory is explored and an approach based on "Interactive Lecture Demonstrations" is proposed.